The Effect of the Training Program to Promote the Knowledge and Awareness of Prospective Preschool Teachers on Emotional Neglect and Abuse - Kanak, Mehmet; Avcı, Neslihan (Asian Journal of Education and Training, 2018)
The aim of the study was to investigate the effect of the “ Training Program to Promote The Knowledge and Awareness of Prospective Preschool Teachers” developed to promote the knowledge and awareness of prospective preschool teachers concerning emotional neglect and abuse. The study group comprised a total of 120 prospective teachers (60 prospective teachers in the experimental group and 60 prospective teachers in the control group) attending Cumhuriyet University, Faculty of Education, Department of Preschool Education in 2014-2015 school year. The pre-test post-test-follow up-test experimental model was used in the study. The “Emotional Neglect/Abuse Knowledge and Awareness Scale” was used to assess the knowledge and awareness of prospective teachers on emotional neglect and abuse, “The Training Program to Promote The Knowledge and Awareness of Prospective Preschool Teachers” was administered to the experimental group whereas the control group received no administration. In data analysis, t-test for related samples was used in pre-test and post-test, and post-test and follow up test comparisons, while a single factor ANOVA with repeated measures was performed for pre-test, post-test and follow up test multiple comparison. Research results revealed a significant difference in favor of the experimental group between the post-test scores of the participants in the experimental and control groups with regard to rejection and ignoring, insulting and exposing the child to violence, isolation and threatening, comparison and discrimination subscales of the “Emotional Neglect/Abuse Knowledge and Awareness Scale” (p<.05). Furthermore, the results of the follow up test administered four weeks after the post-test showed that the effect of the training was still retained (p>.05). In accordance with these results, it was concluded that the research affected prospective teachers’ knowledge and awareness levels of emotional neglect and abuse.